Making sense of infinite uniqueness : the emerging system of idiographic science - Salvatore, Sergio; Gennaro, Alessandro; Valsiner, Jaan (YIS (Series), 2012)
YIS has been thought as an annual series of volumes collecting contributes aimed at developing the integration of idiographic and nomothetic approaches in psychological and more in general social science. At the beginning, 3 years ago, we got an agreement with an Italian publisher (FGP - Firera Publishing Group) interested in the scientific project and therefore willing to help the start up of this scientific enterprise. After publishing the first volume (YIS 2008- yet published in 2009 - the Volume is freely available on the FPG's website) we have had many positive feedbacks and signals of interests, as well as several submissions, from many parts of the world . This has provided an acceleration of the following issues - Above all, this led us to realize that it was time to give an editorial collocation to YIS that can be more consistent with the interest it has raised and that can ulteriorly raise. FPG does not put constraint on this perspective, being aware and agreed of the necessity of a worldwide context for the YIS's development. Moreover, there are no constraints in the possibility of going on in using the label "YIS", starting from Volume 4 The Series addresses a quite large potential public - students and researchers interested to theoretical and methodological development of psychology and, more in general, social science. Persons engaged with qualitative, dynamic informed models of analysis will find YIS a precious tool as well as a context enabling to develop a worlwide network of practices and cultures of research. The first three volumes' TOC witness how large and constantly increasing is the interest around the scientific project.